Properties of bio-oil based fuel mixtures: biochar/bio-oil slurry fuels and glycerol/bio-oil fuel blends - Zhang, Mingming (Curtin University, 2015)
This thesis reports the properties of bio-oil-based fuel mixtures. For bioslurry fuels, the interaction between biochar and bio-oil results in changes in fuel properties and the redistribution of inorganic species. For glycerol/methanol/bio-oil (GMB) fuel blends, the solubility and fuel properties are improved upon methanol addition but other impurities in crude glycerol worsen the solubility with limited impact on properties. It is also possible to integrate the GMB blends production into the biodiesel production process.